Sectoral choice and selectivity - Nirodha Bandara; Simon Appleton; Trudy Owens (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2018)
This paper attempts to examine the labour force participation decisions and earnings across employment sectors and how it varies by gender in Sri Lanka. The labour market is disaggregated into 5 sectors - public, formal private, informal private, self-employed and agriculture. Using the Labour Force Survey 2013, this paper adds to existing literature in two ways. Firstly, the paper deals with two forms of potential biases which have not been simultaneously explored for the case of Sri Lanka - sample selectivity and endogeneity of education in earnings. Secondly, it adds to the literature by including the self-employed in the analysis. The determinants of sector choice are analysed using a multinomial logit. The findings of this paper suggest that individuals with the highest levels of education get into the public and formal private sectors, whereas the least educated are likely to join the informal and agricultural sectors. The earnings functions suggest that the returns to education vary greatly across the sectors. The differences across sectors confirm the importance of disaggregating the sectors of employment to examine choices of labour force participation.
Keywords: C3; J24; O12; 330; sample selectivity; endogeneity; multinomial logit; control function; Sri Lanka